Optimizing targeted therapy for metastatic melanoma: a combination of encorafenib and trametinib beyond standard protocols (Dermatology Reports, 2025)
Only three combinations of BRAF inhibitor (BRAFi) and MEK inhibitor (MEKi) targeted therapies are marketed for the treatment of BRAF-mutated metastatic melanoma. The use of these combinations can be limited by the occurrence of severe adverse events (AEs) that may lead to discontinuation of treatment or contraindication. We present the case of a 45-year-old male diagnosed with stage III melanoma of the left thigh, as classified by the 8th edition of the American Joint Committee on Cancer (AJCC), exhibiting rapid recurrence of inguinal lymph node metastasis following complete surgical resection. Molecular biology revealed a mutated BRAFV600E status, indicating treatment associated with BRAFi/MEKi. First-line treatments were introduced successively with dabrafenib-trametinib and then encorafenib-binimetinib, both stopped for fever and severe digestive AEs. After the failure of a third line with an immune checkpoint inhibitor, a new rechallenge of targeted therapy (TT) was introduced with encorafenib-trametinib to increase tolerance. This unusual and innovative combination allowed a spectacular tolerance and complete oncological response for 39 months after the failure of the usual combinations. This is the first case in the literature to show the potential efficacy of a non-standard combination of encorafenib and trametinib, which are commercialized in two different market combinations. A pharmacological evidence-based analysis was performed to understand these good clinical results.